A Comparative Study on the Central Library Websites of Iranian State Universities in HTML and Dublin Core Metadata Element Usage - Mahtab Ramezan Shirazi (مدیریت اطلاعات سلامت, 2013)
Introduction: Recent progress in providing innovative solutions in the organization of electronic resources and research in this area shows the global trend in the use of new strategies such as metadata to facilitate descripting, locating, organizing, and searching resources in the web environment. In this context, library metadata standards are of great importance. Therefore, the purpose of the present study was to compare the central library websites of Iranian state universities in terms of HTML and Dublin Core metadata elements usage in 2011.